L’université de Strasbourg dans l’immédiat après-guerre (1919-1925) - Bertrand Müller (Revue d’Histoire des Sciences Humaines)
The University of Strasbourg is an interesting laboratory for observing university reconfigurations in the immediate post-war period. Thought as a French anti-model of the German experience but also as a laboratory that must point the way to a university reform in France, it is imagined not only as a Rhine model against Germany, but as an international model and European. Yet, taken in international and national and regional political and cultural issues, the University of Strasbourg has been confronted with the situation of Franco-German relations and a problem of scale. The years immediately after the war are a singular moment during which an environment of debate is organized rather than rebuilding a place of renovation, quickly thwarted by political and financial constraints.